2011
DOI: 10.1021/om1008555
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Gold and Platinum Menthyl Complexes

Abstract: A Grignard reagent derived from (−)-menthyl chloride has been reported to be a 1:1 mixture of menthyl magnesium chloride and neomenthyl magnesium chloride, which do not interconvert. Addition of an excess of this reagent to Au(PPh3)(Cl) or Pt(dppe)Cl2 gave Au(PPh3)(Men) (1) and Pt(dppe)(Men)(Br) (2), respectively. Crystallographic studies of these first well-characterized transition metal menthyl complexes showed that the menthyl group adopts a conformation with all three substituents in equatorial positions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The bulkier (−)-menthyl derivative 6 produced (−)-menthyl fluoride as the exclusive product with perfect stereoretention and with no evidence of alkene products. 16 Surprisingly, β-H elimination outcompeted C–F reductive elimination for cyclopentyl derivative 7 . For the more strained cycloalkyl derivatives 8 and 9 , β-H elimination pathways were marginalized but carbocation-like rearrangement processes were observed as minor pathways relative to direct C–F reductive elimination.…”
Section: Resultsmentioning
confidence: 99%
“…The bulkier (−)-menthyl derivative 6 produced (−)-menthyl fluoride as the exclusive product with perfect stereoretention and with no evidence of alkene products. 16 Surprisingly, β-H elimination outcompeted C–F reductive elimination for cyclopentyl derivative 7 . For the more strained cycloalkyl derivatives 8 and 9 , β-H elimination pathways were marginalized but carbocation-like rearrangement processes were observed as minor pathways relative to direct C–F reductive elimination.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative approach to determine the stereochemistry of cyclopropanation with respect to Cα, we targeted the cis -3-methoxycyclohexyl gold complex cis -( P )­AuCHCH 2 CH­(OMe)­CH 2 CH 2 CH 2 ( cis - 7 ). This approach was inspired by the work of Glueck and co-workers, who reported the stereoselective formation of the all equatorial gold menthyl complex (PPh 3 )­AuCHCH 2 CH­(Me)­CH 2 CH 2 CH­(CHMe 2 ) via transmetalation of Ph 3 PAuCl with the Grignard reagent derived from (−)­menthyl chloride . Because both the ( P )Au moiety and methoxy groups of cis - 7 would presumably occupy equatorial orientations, cis - 7 would be particularly susceptible to cyclopropanation via a double inversion mechanism upon treatment with Lewis acid (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Transmetalation of ( P )­AuCl with the Grignard reagent generated from cis -1-chloro-3-methoxycyclohexane led to isolation of cis- 7 in 20% yield as a single diastereomer as determined by 1 H and 31 P NMR analysis. The 13 C NMR spectrum of cis - 7 displayed a diagnostic doublet at δ 42.7 (d, J = 99.2 Hz) assigned to the gold-bound carbon atom. , The equatorial orientation of both the ( P )Au and methoxy groups of cis - 7 was established by the presence of large 3 J HH axial–axial coupling constants for both the Hα (δ 0.58, J = 12.5 Hz) and Hγ protons (δ 2.76, J = 10.3) in the 1 H NMR spectrum. Treatment of cis - 7 with TMSOTf/pyridine (10:1) at −78 °C led to immediate formation of a 5.1:1 mixture of bicyclo[3.1.0]­hexane and cyclohexyl methyl ether in 98 ± 5% combined yield as determined by 1 H NMR spectroscopy (Scheme ), thereby validating a double inversion mechanism for the cyclopropanation of γ-methoxy gold alkyl complexes.…”
Section: Resultsmentioning
confidence: 99%
“…11a,d,16 The reagent has also been used in cross-coupling 17,18 or transmetalation reactions. 19 The products tend to retain menthyl configuration, and the sequence from 2 via 1 to various substitution products (Men-E) has usually been assumed to proceed with retention of configuration in all steps (Scheme 1). 8,9,14,20,21 The occasional observation of epimeric products (Nmn-E) as minor components revealed that retention is not strict.…”
Section: ■ Introductionmentioning
confidence: 99%